EVOLUTION OF THE PHYSICAL EDUCATION SYSTEM THROUGH THE PRISM OF HISTORY - Orishev A.B. ,; Mamedov A.A. ,; Mironyuk S.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine the place and role of physical education and sports in the system of agricultural education in the USSR and the Russian Federation, carrying out their comparative analysis. Methods and structure of the study. The following methods were used in the work: included and non-involved observation of physical education teachers, interviews with physical education teachers and sports coaches, a sociological survey of first-year students. The example of the leading agricultural university of the country – Timiryazev Academy – shows the evolution of approaches to teaching physical education in the USSR and the Russian Federation. Results and conclusions. Data on the teaching of physical education at Timiryazev Academy in different periods of its history are provided. The results of a sociological survey among students of Timiryazev Academy are highlighted, according to which the overwhelming majority of students have a positive attitude towards the GTO standards, which were the normative basis of the Soviet system of physical education. The University has a Physical Education and Sports Development Program for 2021–2030, one of the areas of which is the popularization of the All-Russian Physical Education and Sports Complex “Ready for Labor and Defense”. The main scientific result: the timeliness of turning to the positive developments of the Soviet era is substantiated, but taking into account modern realities. This is the approach implemented at the Timiryazev Academy.